Existence and multiplicity of positive solutions for one-dimensional prescribed mean curvature equations

  • Yanqiong Lu1,

    Affiliated with

    • Ruyun Ma1Email author and

      Affiliated with

      • Hongliang Gao1

        Affiliated with

        Boundary Value Problems20142014:120

        DOI: 10.1186/1687-2770-2014-120

        Received: 3 January 2014

        Accepted: 6 May 2014

        Published: 16 May 2014

        Abstract

        In this work, we establish the existence and multiplicity results of positive solutions for one-dimensional prescribed mean curvature equations. Our approach is based on fixed point index theory for completely continuous operators which leave invariant a suitable cone in a Banach space of continuous functions.

        MSC:34B10, 34B18.

        Keywords

        mean curvature equations positive solutions existence fixed point index

        1 Introduction

        The prescribed mean curvature problems like
        { div ( D u 1 + κ ( D u ) 2 ) = f ( x , u ) , x Ω , u = 0 , x Ω
        have attracted much attention in recent years, see [14] and the references therein. Since the problem is quasilinear non-uniformly elliptic, it is more difficult to study the existence of classical solutions. The greatest obstacle is the lack of gradient estimate, such kind of estimate does not hold in general and boundary gradient blow-up may occur. This leads to some new phenomena very different from those in semilinear problems. Many well-known results of semilinear problems have to be reconsidered for this quasilinear problem. Motivated by the search for solutions of the above problem, many authors (see [513]) studied the existence of (positive) solutions for one-dimensional prescribed mean curvature equations with Dirichlet boundary conditions
        { ( u 1 + κ ( u ) 2 ) = λ f ( u ) , x ( 0 , 1 ) , u ( 0 ) = u ( 1 ) = 0 ,
        (1.1)

        where κ > 0 is a constant, f C ( [ 0 , ) , [ 0 , ) ) and f ( u ) > 0 for u > 0 and x [ 0 , 1 ] .

        Note that if κ = 0 , problem (1.1) is degenerate to the second-order ordinary differential equation boundary value problems
        { u = λ f ( u ) , x ( 0 , 1 ) , u ( 0 ) = u ( 1 ) = 0 .
        (1.2)

        The existence of (positive) solutions of (1.1) has been well known with various qualitative assumptions of the nonlinearity f, see [14, 15] and the references therein.

        If κ = 1 , Bonheure et al. [6], Habets and Omari [9], Kusahara and Usami [10], Pan and Xing [12, 13] studied the existence of (positive) solutions of (1.2) by using the variational method, lower and upper solutions method and time mapping method, respectively.

        However, to the best of our knowledge, the existence and multiplicity of positive solutions for (1.1) are relatively few by the fixed point index theory. In this paper, based on the fixed point index theory, we shall investigate the existence and multiplicity of positive solution of (1.1) when f is ϕ-superlinear and ϕ-sublinear at 0 and ∞, respectively, here ϕ ( s ) = s 1 + κ s 2 .

        Let ϕ ( s ) = s 1 + κ s 2 . Then (1.1) can be rewritten as
        { ( ϕ ( u ) ) = λ f ( u ( x ) ) , x ( 0 , 1 ) , u ( 0 ) = u ( 1 ) = 0 .
        (1.3)

        Obviously, ϕ : R ( 1 κ , 1 κ ) is an odd, increasing homeomorphism with ϕ ( 0 ) = 0 .

        For convenience, we introduce some notations
        f 0 = lim u 0 f ( u ) ϕ ( u ) and f = lim u f ( u ) ϕ ( u ) .

        We will also need the function f ( u ) = max 0 t u { f ( t ) } , and let f 0 = lim u 0 f ( u ) ϕ ( u ) . By a similar method in [[14], Lemma 2.8], it is not difficult to verify that f 0 = f 0 .

        In the rest of this paper, we shall study the existence of positive solutions of (1.3) by using the fixed point index theory to give a brief and clear proof for the existence of positive solutions of (1.1). More concretely, we shall prove the following.

        Theorem 1.1 Assume that f C ( [ 0 , ) , [ 0 , ) ) and f ( u ) > 0 for u > 0 .
        1. (i)

          If f 0 = 0 , then there exists 0 < λ < λ such that (1.1) has a positive solution for λ < λ < λ .

           
        2. (ii)

          If f 0 = , then there exists λ 0 > 0 such that (1.1) has a positive solution for 0 < λ < λ 0 .

           
        3. (iii)

          If f 0 = f = 0 , then there exists 0 < λ < λ such that (1.1) has at least two positive solutions for λ < λ < λ .

           
        4. (iv)

          If f 0 = f = , then there exists 0 < λ < λ such that (1.1) has at least two positive solutions for λ < λ < λ .

           
        Corollary 1.2 Assume that f C ( [ 0 , ) , [ 0 , ) ) and f ( u ) > 0 for u > 0 .
        1. (a)

          If f 0 = 0 and f = , then there exists 0 < λ < λ such that (1.1) has a positive solution for λ < λ < λ .

           
        2. (b)

          If f 0 = and f = 0 , then there exists λ 0 > 0 such that (1.1) has a positive solution for 0 < λ < λ 0 .

           

        Remark 1.1 The results of Theorem 1.1 and Corollary 1.2 are different with the case κ = 0 which is the classical Dirichlet boundary value problem (1.2). This phenomenon is a striking feature of problem (1.1), which is just the reason why we study the existence of positive solutions of problem (1.1). It is pointed out that in equation of (1.1), having replaced f ( u ) with f ( x , u ) , Theorem 1.1 and Corollary 1.2 also hold as well as all of the proofs with obvious changes.

        2 Preliminaries

        Throughout the paper | | will denote absolute value, and let
        E = { u C [ 0 , 1 ] u ( 0 ) = u ( 1 ) = 0 } .

        Then E is a Banach space endowed with the norm u = max x [ 0 , 1 ] | u ( x ) | .

        We first establish some preliminary results to prove our main result. An easy but useful property of ϕ and ϕ 1 is the following one.

        Lemma 2.1 Let ϕ ( s ) = s 1 + κ s 2 . Then ϕ : R ( 1 κ , 1 κ ) is an odd, increasing homeomorphism with ϕ ( 0 ) = 0 . Moreover, ϕ has the following properties:
        1. (i)

          ϕ is convex up on [ 0 , ) and ϕ 1 is concave up on ( 0 , 1 κ ) .

           
        2. (ii)

          For each c 1 , there exists A ˆ c c such that ϕ ( c s ) A ˆ c ϕ ( s ) , s 0 with lim c A ˆ c = and for each 0 < c 1 , there exists 0 < B ˆ c c such that ϕ ( c s ) B ˆ c ϕ ( s ) , s 0 with lim c 0 B ˆ c = 0 .

           
        3. (iii)

          For each 0 < c 1 , there exists B c c such that ϕ 1 ( c s ) B c ϕ 1 ( s ) , s ( 0 , 1 κ ) . For each c 1 with 1 κ < c s < 1 κ , there exists A c c such that ϕ 1 ( c s ) A c ϕ 1 ( s ) , s ( 0 , 1 κ ) .

           
        Proof By a simple computation, it follows that ϕ ( s ) = ϕ ( s ) and ϕ ( s ) = 1 ( 1 + κ s 2 ) 3 > 0 . So ϕ is an odd, increasing homeomorphism with ϕ ( 0 ) = 0 . Moreover, from ϕ ( s ) = 3 κ s ( 1 + κ s 2 ) 5 , we get that ϕ is convex up on [ 0 , ) . Notice that ϕ 1 ( s ) = s 1 κ s 2 is also an odd, increasing homeomorphism with ϕ ( 0 ) = 0 . It is easy to verify that ϕ 1 is concave up on ( 0 , 1 κ ) .
        1. (ii)
          For each 0 < c 1 , there exists B ˆ c c such that
          ϕ ( c s ) = c s 1 + κ c 2 s 2 B ˆ c s 1 + κ s 2 , s 0 ;
           
        and for each c 1 , there exists A ˆ c c such that
        ϕ ( c s ) = c s 1 + κ c 2 s 2 A ˆ c s 1 + κ s 2 , s 0 .
        1. (iii)

          By a similar argument, it is not difficult to compute that for each 0 < c 1 , there exists B c c such that ϕ 1 ( c s ) B c ϕ 1 ( s ) , s ( 0 , 1 κ ) . For each c 1 with 1 κ < c s < 1 κ , there exists A c c such that ϕ 1 ( c s ) A c ϕ 1 ( s ) , s ( 0 , 1 κ ) . □

           
        Lemma 2.2 Let h C ( [ 0 , 1 ] , [ 0 , ) ) with h 0 . Assume that w is the solution of
        { ( ϕ ( u ) ) = h ( x ) , x ( 0 , 1 ) , u ( 0 ) = u ( 1 ) = 0 .
        (2.1)

        Then w > 0 on ( 0 , 1 ) and w ϕ 1 ( M ) , where M = min { 1 κ , sup x [ 0 , 1 ] | h ( x ) | } .

        Proof By integrating, it follows that (2.1) has the unique solution given by
        w ( x ) = 0 x ϕ 1 ( C 0 s h ( t ) d t ) d s ,

        where C is such that w ( 1 ) = 0 . Hence we must have 0 < C < 0 1 h ( t ) d t . Further, since ϕ ( u ) ( 1 κ , 1 κ ) , by using ϕ ( w ( x ) ) = C 0 x h ( t ) d t , we obtain M ϕ ( w ( x ) ) M , x [ 0 , 1 ] and w ϕ 1 ( M ) follows, here M = min { 1 κ , sup x [ 0 , 1 ] | h ( x ) | } .

        Since w ( 0 ) = w ( 1 ) = 0 , there exists x 0 ( 0 , 1 ) such that w ( x 0 ) = 0 and it follows from ( ϕ ( w ) ) 0 that ϕ ( w ) is decreasing on ( 0 , 1 ) . Then w ( x ) > 0 for x < x 0 and w ( x ) < 0 for x > x 0 . Hence, w > 0 on ( 0 , 1 ) . □

        Note that from Lemma 2.2, there exists τ i ( 0 , 1 2 ) , i = 1 , 2 , such that min x [ τ 1 , 1 τ 2 ] w ( x ) σ w with 0 < σ < 1 depending on τ i . Define the cone P in E by
        P = { u E | u ( x ) 0  on  [ 0 , 1 ]  and  min x [ τ 1 , 1 τ 2 ] u ( x ) σ u } ,

        and for r > 0 , let Ω r = { u P u < r } .

        Lemma 2.3 ([[11], Lemma 4.1 and Lemma 4.2])

        For each h C [ 0 , 1 ] , (2.1) has a unique solution given by
        u ( x ) = 0 x ϕ 1 ( C 0 s h ( t ) d t ) d s = : T h ( u ) ( x ) ,

        where C is such that u ( 1 ) = 0 with 0 < C < 0 1 h ( t ) d t . Moreover, the operator T h : E E is continuous and sends equicontinuous sets in C [ 0 , 1 ] into a relatively compact set in E.

        We next state the fixed point index theorem which will be used to prove our results.

        Lemma 2.4 ([[16], Chapter 6])

        Let E be a Banach space and P be a cone in E. Assume that Ω is a bounded open subset of E with 0 Ω , and let T : P Ω ¯ P be a completely continuous operator such that T u u , u Ω P .
        1. (i)

          If T u u , u Ω P , then i ( A , Ω P , P ) = 1 .

           
        2. (ii)

          If T u u , u Ω P , then i ( A , Ω P , P ) = 0 .

           
        From Lemma 2.2, problem (1.3) is equivalent to the fixed point problem
        u ( x ) = 0 x ϕ 1 ( C 0 λ 0 s f ( u ( t ) ) d t ) d s : = T λ ( u ) ( x )
        in the space E, where C 0 is such that u ( 1 ) = 0 with 0 < C 0 < λ 0 1 f ( u ( t ) ) d t , since otherwise,
        u ( 1 ) = 0 1 ϕ 1 ( C 0 λ 0 s f ( u ( t ) ) d t ) d s 0 1 ϕ 1 ( λ s 1 f ( u ( t ) ) d t ) d s > 0 ,
        which is a contradiction. This together with Lemma 2.3 implies that T λ : E E is a completely continuous mapping. Moreover, for any fixed u P , we have
        T λ ( u ) ( x ) = 0 x ϕ 1 ( C 0 λ 0 s f ( u ( t ) ) d t ) d s 0 , x [ 0 , 1 ]
        (2.2)

        and T λ ( u ) ( 0 ) = T λ ( u ) ( 1 ) = 0 . In addition, from Lemma 2.2, it follows that T λ ( u ) ( x ) > 0 on ( 0 , 1 ) and there exist τ i ( 0 , 1 2 ) , i = 1 , 2 , such that min x [ τ 1 , 1 τ 2 ] T λ u σ T λ u . So T λ : P P is a completely continuous operator.

        Lemma 2.5 Let r > 0 be given. If there exists ε > 0 small enough with B λ ε < 1 such that f ( r ) ε ϕ ( r ) , then
        T λ u B λ ε u for  u Ω r ,

        where B λ ε is defined as in Lemma  2.1(iii).

        Proof From the definition of T λ , for any u Ω r , we have
        T λ u = max x [ 0 , 1 ] | 0 x ϕ 1 ( C 0 λ 0 s f ( u ( t ) ) d t ) d s | 0 1 ϕ 1 ( λ s 1 f ( u ( t ) ) d t ) d s 0 1 ϕ 1 ( λ s 1 f ( r ) d t ) d s 0 1 ϕ 1 ( λ ε ϕ ( r ) ) d s B λ ε r .

         □

        Lemma 2.6 Let η > 0 be given. If u P and f ( u ( x ) ) η ϕ ( u ( x ) ) for x [ 0 , 1 ] , then
        T λ u σ x ϕ 1 ( λ ( 1 σ ) x η ϕ ( σ u ) ) ,

        where x = min { x 0 , 1 x 0 } and u ( x 0 ) = max x [ 0 , 1 ] u ( x ) = u .

        Proof From problem (1.3), since u ( 0 ) = u ( 1 ) = 0 , it follows that there exists x 0 ( 0 , 1 ) such that u ( x 0 ) = 0 . Let u = u ( x 0 ) . Then u satisfies the following boundary value problem:
        { ( ϕ ( u ( x ) ) ) = λ f ( u ( x ) ) , x ( 0 , x 0 ) , u ( 0 ) = 0 , u ( x 0 ) = u .
        (2.3)
        Let v be the solution of the problem
        { ( ϕ ( v ( x ) ) ) = 0 , x ( 0 , x 0 ) , v ( 0 ) = 0 , v ( x 0 ) = u .
        (2.4)
        Then we have
        { ( ϕ ( u ( x ) ) ϕ ( v ( x ) ) ) = λ f ( u ( x ) ) , x ( 0 , x 0 ) , ( u v ) ( 0 ) = 0 , ( u v ) ( x 0 ) = 0 ,
        (2.5)
        and by a comparison argument, we get that u > v on ( 0 , x 0 ) . In fact, from ( u v ) ( 0 ) = 0 , ( u v ) ( x 0 ) = 0 , there exists x ˆ ( 0 , x 0 ) such that ( u v ) ( x ˆ ) = 0 , i.e., u ( x ˆ ) = v ( x ˆ ) . Thus, by a simple computation, we have that
        ϕ ( u ( x ) ) = ϕ ( v ( x ) ) + x x ˆ λ f ( u ( t ) ) d t ϕ ( v ( x ) ) for  x ( 0 , x ˆ )
        and
        ϕ ( v ( x ) ) = ϕ ( u ( x ) ) + x ˆ x λ f ( u ( t ) ) d t ϕ ( u ( x ) ) for  x ( x ˆ , x 0 ) .
        This together with ϕ is an increasing homeomorphism implies that
        u ( x ) v ( x ) for  x ( 0 , x ˆ ) ,
        (2.6)
        v ( x ) u ( x ) for  x ( x ˆ , x 0 ) .
        (2.7)

        Integrating from 0 to x for (2.6) and integrating from x to x 0 for (2.7), respectively, we have that u ( x ) v ( x ) for x [ 0 , x 0 ] .

        Note that
        v ( x ) = u x x 0 ϕ 1 ( C 1 ) d s ,
        where C 1 is such that v ( 0 ) = 0 , and hence u = 0 x 0 ϕ 1 ( C 1 ) d s . If C 1 > ϕ ( u x 0 ) , then it follows that
        u = 0 x 0 ϕ 1 ( C 1 ) d s > 0 x 0 ϕ 1 ( ϕ ( u x 0 ) ) d s u ,
        which is a contradiction. Thus, 0 C 1 ϕ ( u x 0 ) . Moreover, we have
        v ( x ) = u x x 0 ϕ 1 ( C 1 ) d s u ( x 0 x ) ϕ 1 ( ϕ ( u x 0 ) ) = x x 0 u , x [ x 1 , x 0 ] ,
        where x 1 = σ x 0 . Consequently, u ( x ) v ( x ) σ u for x [ x 1 , x 0 ] . Obviously,
        u ( x ) = 0 x ϕ 1 ( C 2 λ 0 s f ( u ( t ) ) d t ) d s ,
        where C 2 satisfies u ( x 0 ) = 0 . It follows from ϕ 1 ( C 2 λ 0 x 0 f ( u ( t ) ) d t ) = 0 that C 2 = λ 0 x 0 f ( u ( t ) ) d t . Therefore,
        u ( x ) = 0 x ϕ 1 ( λ s x 0 f ( u ( t ) ) d t ) d s = T λ u ( x ) , x [ 0 , x 0 ] .
        (2.8)
        If x 0 1 2 , then
        T λ u 0 x 1 ϕ 1 ( λ s x 0 f ( u ( t ) ) d t ) d s 0 x 1 ϕ 1 ( λ x 1 x 0 η ϕ ( u ( t ) ) d t ) d s 0 x 1 ϕ 1 ( λ ( x 0 x 1 ) η ϕ ( σ u ) ) d s σ x 0 ϕ 1 ( λ ( 1 σ ) x 0 η ϕ ( σ u ) ) .
        If x 0 1 2 , let w be the solution of
        ( ϕ ( w ( x ) ) ) = 0 , x ( x 0 , 1 ) , w ( x 0 ) = u , w ( 1 ) = 0 .
        (2.9)
        Then
        w ( x ) = u + x 0 x ϕ 1 ( C 3 ) d s ,
        where C 3 < 0 satisfies w ( 1 ) = 0 , i.e., u = x 0 1 ϕ 1 ( C 3 ) d s . If C 3 < ϕ ( u 1 x 0 ) , then
        u = x 0 1 ϕ 1 ( C 3 ) d s > x 0 1 ϕ 1 ( ϕ ( u 1 x 0 ) ) d s u ,

        which is contradiction. Hence ϕ ( u 1 x 0 ) C 3 0 .

        By a similar argument as before, it follows that u w on ( x 0 , 1 ) . Moreover,
        w ( x ) = u + x 0 x ϕ 1 ( C 3 ) d s u + ( x x 0 ) ϕ 1 ( ϕ ( u 1 x 0 ) ) = 1 x 1 x 0 u , x [ x 0 , x 2 ] ,
        where x 2 = 1 σ ( 1 x 0 ) . So u ( x ) w ( x ) σ u , x [ x 0 , x 2 ] . Therefore, we have
        u ( x ) = x 1 ϕ 1 ( λ x 0 s f ( u ( t ) ) d t ) d s = T λ u ( x ) , x [ x 0 , 1 ] ,
        (2.10)
        and subsequently,
        T λ u x 2 1 ϕ 1 ( λ x 0 s f ( u ( t ) ) d t ) d s x 2 1 ϕ 1 ( λ x 0 x 2 η ϕ ( u ( t ) ) d t ) d s x 2 1 ϕ 1 ( λ ( x 2 x 0 ) η ϕ ( σ u ) ) d s σ ( 1 x 0 ) ϕ 1 ( λ ( 1 σ ) ( 1 x 0 ) η ϕ ( σ u ) ) .
        Let x = min { x 0 , 1 x 0 } . Then
        T λ u σ x ϕ 1 ( λ ( 1 σ ) x η ϕ ( σ u ) ) .

         □

        Lemma 2.7 Let r > 0 be given. If u Ω r , then
        T λ u ϕ 1 ( λ M r ) ,

        where M r = 1 + max 0 u r { f ( u ) } > 0 .

        Proof Obviously, for any u Ω r , it follows that f ( u ( x ) ) M r for x [ 0 , 1 ] . So we have
        T λ u 0 1 ϕ 1 ( λ s 1 f ( u ( t ) ) d t ) d s ϕ 1 ( λ M r ) .

         □

        Lemma 2.8 Let r > 0 be given. If u Ω r , then
        T λ u σ x ϕ 1 ( λ ( 1 σ ) x m r ) ,

        where m r = min σ r u r { f ( u ) } > 0 and x = min { x 0 , 1 x 0 } .

        Proof By using a similar argument of the proof of Lemma 2.6, we have that u ( x ) σ u for x [ x 1 , x 2 ] . Meanwhile, (2.8) is true. If x 0 1 2 , then we can get that
        T λ u 0 x 1 ϕ 1 ( λ s x 0 f ( u ( t ) ) d t ) d s 0 x 1 ϕ 1 ( λ x 1 x 0 m r d t ) d s 0 x 1 ϕ 1 ( λ ( x 0 x 1 ) m r ) d s x 1 ϕ 1 ( λ ( x 0 x 1 ) m r ) = σ x 0 ϕ 1 ( λ ( 1 σ ) x 0 m r ) .
        If x 0 1 2 , then (2.10) holds and it follows that
        T λ u x 2 1 ϕ 1 ( λ x 0 s f ( u ( t ) ) d t ) d s x 2 1 ϕ 1 ( λ x 0 x 2 m r d t ) d s x 2 1 ϕ 1 ( λ ( x 2 x 0 ) m r ) d s ( 1 x 2 ) ϕ 1 ( λ ( x 2 x 0 ) m r ) = σ ( 1 x 0 ) ϕ 1 ( λ ( 1 σ ) ( 1 x 0 ) m r ) .
        Let x = min { x 0 , ( 1 x 0 ) } , then
        T λ u σ x ϕ 1 ( λ ( 1 σ ) x m r ) .

         □

        3 Proof of the main results

        Proof of Theorem 1.1 (i) Choose a suitable number r 1 > 0 . By Lemma 2.8, we have
        T λ u > u for  u Ω r 1  and  λ < λ < λ ,
        where
        λ 1 κ ( 1 σ ) x m r 1 and λ 1 ( 1 σ ) x m r 1 ϕ ( r 1 σ x ) .
        If f 0 = 0 , then f 0 = 0 , and so we can choose r 2 ( 0 , r 1 ) such that f ( r 2 ) ε ϕ ( r 2 ) , where ε > 0 small enough satisfies
        B λ ε < 1 .
        (3.1)
        Then Lemma 2.5 implies that
        T λ u < u for  u Ω r 2 .
        From Lemma 2.4, it follows that i ( T λ , Ω r 1 , P ) = 0 and i ( T λ , Ω r 2 , P ) = 1 . By using the additivity-excision property of the fixed point index [16], we have that
        i ( T λ , Ω r 1 Ω ¯ r 2 , P ) = i ( T λ , Ω r 1 , P ) i ( T λ , Ω r 2 , P ) = 1 .
        Therefore, T λ has a fixed point in Ω ¯ r 1 Ω r 2 . Consequently, (1.1) has a positive solution for λ < λ < λ .
        1. (ii)
          Choose a suitable number r 1 > 0 . By Lemma 2.7, there exists
          0 < λ 0 min { 1 κ M r 1 , ϕ ( r 1 ) M r 1 } = ϕ ( r 1 ) M r 1
           

        such that T λ u < u for u Ω r 1 and 0 < λ < λ 0 . That is, i ( T λ , Ω r 1 , P ) = 1 .

        If f 0 = , then there exists r 2 ( 0 , r 1 ) such that f ( u ) η ϕ ( u ) for 0 u r 2 , where η > 0 is chosen large enough so that
        λ ( 1 σ ) x η ϕ ( σ r 2 ) < 1 κ and σ 2 λ ( 1 σ ) x 2 η > 1 .
        (3.2)
        Clearly, f ( u ) η ϕ ( u ( x ) ) for u Ω r 2 , x [ 0 , 1 ] . From Lemma 2.6, we get that
        T λ u σ x ϕ 1 ( λ ( 1 σ ) x η ϕ ( σ u ) ) σ 2 λ ( 1 σ ) x 2 η u > u for  u Ω r 2 .
        This together with Lemma 2.4 implies i ( T λ , Ω r 2 , P ) = 0 . By using the additivity-excision property of the fixed point index [16], we have
        i ( T λ , Ω r 1 Ω ¯ r 2 , P ) = i ( T λ , Ω r 1 , P ) i ( T λ , Ω r 2 , P ) = 1 .
        Therefore, T λ has a fixed point in Ω ¯ r 1 Ω r 2 . Consequently, (1.1) has a positive solution for 0 < λ < λ 0 .
        1. (iii)
          Since ϕ is a bounded operator, multiplying (1.3) by u and integrating from 0 to x 0 , we get that
          λ 0 u ( x 0 ) f ( u ) d u = 1 κ [ 1 1 1 + κ ( u ( 0 ) ) 2 ] 1 κ as  u ( 0 ) .
           
        Let λ > 0 be the solution of λ 0 r f ( u ) d u = 1 κ . Then there exists r ¯ : = r ϵ > 0 such that
        λ 0 r ¯ f ( u ) d u < 1 κ
        (3.3)

        with r ¯ = u ( x 0 ) = u .

        Choose two numbers 0 < r 3 < r 4 < r ¯ satisfying
        ϕ ( r 3 σ x ) < ( 1 σ ) x m r 3 M r ¯ ϕ ( r ¯ ) and ϕ ( r 4 σ x ) < ( 1 σ ) x m r 4 M r ¯ ϕ ( r ¯ ) .
        By Lemma 2.8, there exist
        λ = max { ϕ ( r 3 σ x ) ( 1 σ ) x m r 3 , ϕ ( r 4 σ x ) ( 1 σ ) x m r 4 }
        and
        λ = min { 1 κ M r ¯ , ϕ ( r ¯ ) M r ¯ , 1 ( 1 σ ) x m r 3 κ , 1 ( 1 σ ) x m r 4 κ } = ϕ ( r ¯ ) M r ¯
        such that for λ < λ < λ , we have
        T λ u > u for  u Ω r i , i = 3 , 4 .

        This together with Lemma 2.4 implies i ( T λ , Ω r i , P ) = 0 , i = 3 , 4 .

        Since f 0 = 0 , from the proof of the case (i), it follows that we can choose r 1 ( 0 , r 3 2 ) such that i ( T λ , Ω r 1 , P ) = 1 . Subsequently,
        i ( T λ , Ω r 3 Ω ¯ r 1 , P ) = i ( T λ , Ω r 3 , P ) i ( T λ , Ω r 1 , P ) = 1 .
        On the other hand, f = 0 , λ < λ and (3.3) together with Lemma 2.7 implies
        T λ u ϕ 1 ( λ M r ¯ ) < u for any  u Ω r ¯ .
        That is, i ( T λ , Ω r ¯ , P ) = 1 . Subsequently,
        i ( T λ , Ω r ¯ Ω ¯ r 4 , P ) = i ( T λ , Ω r ¯ , P ) i ( T λ , Ω r 4 , P ) = 1 .
        Therefore, T λ has two fixed points u 1 and u 2 such that u 1 Ω ¯ r 3 Ω r 1 and u 2 Ω ¯ r ¯ Ω r 4 . These are the desired distinct positive solutions of (1.1) for λ < λ < λ satisfying
        r 1 u 1 r 3 < r 4 u 2 r 2 .
        (3.4)
        1. (iv)
          Choose two numbers 0 < r 3 < r 4 < r ¯ satisfying
          ϕ ( r 3 ) > M r 3 ( 1 σ ) x m r ¯ ϕ ( r ¯ σ x ) and ϕ ( r 4 ) > M r 4 ( 1 σ ) x m r ¯ ϕ ( r ¯ σ x ) .
           
        By Lemma 2.7, there exists 0 < λ 0 min { ϕ ( r 3 ) M r 3 , ϕ ( r 4 ) M r 4 } such that for 0 < λ < λ 0 , we have
        T λ u < u for  u Ω r i , i = 3 , 4 .

        That is, i ( T λ , Ω r 3 , P ) = 1 and i ( T λ , Ω r 4 , P ) = 1 .

        Since f 0 = , from the proof of the case (ii), choose r 1 ( 0 , r 3 2 ) such that i ( T λ , Ω r 1 , P ) = 0 . Consequently,
        i ( T λ , Ω r 3 Ω ¯ r 1 , P ) = i ( T λ , Ω r 3 , P ) i ( T λ , Ω r 1 , P ) = 1 .
        On the other hand, f = and (3.3) together with Lemma 2.8 implies that
        T λ u σ x ϕ 1 ( λ ( 1 σ ) x m r ¯ ) .
        Let λ = ϕ ( r ¯ σ x ) ( 1 σ ) x m r ¯ and λ = min { λ 0 , 1 κ ( 1 σ ) x m r ¯ } . Then, for any λ < λ < λ , we have
        T λ u > u for any  u u Ω r ¯ .
        That is, i ( T λ , Ω r ¯ , P ) = 0 . Subsequently,
        i ( T λ , Ω r ¯ Ω ¯ r 4 , P ) = i ( T λ , Ω r ¯ , P ) i ( T λ , Ω r 4 , P ) = 1 .

        Therefore, T λ has two fixed points u 1 and u 2 such that u 1 Ω ¯ r 3 Ω r 1 and u 2 Ω ¯ r ¯ Ω r 4 . These are the desired distinct positive solutions of (1.1) for λ < λ < λ satisfying (3.4). □

        Proof of Corollary 1.2 It is easy to show by the result of Theorem 1.1(i) and (ii). □

        Example 3.1 Let us consider the following problem:
        { ( u 1 + κ ( u ) 2 ) = λ e u , x ( 0 , 1 ) , u ( 0 ) = u ( 1 ) = 0 .
        (3.5)

        Obviously, f 0 = lim u 0 e u ϕ ( u ) = and f = lim u e u ϕ ( u ) = . From Theorem 1.1(iv), there exists 0 < λ < λ such that (3.5) has at least two positive solutions for λ < λ < λ .

        Example 3.2 Let us consider the following problem:
        { ( u 1 + κ ( u ) 2 ) = λ u p , x ( 0 , 1 ) , u ( 0 ) = u ( 1 ) = 0 .
        (3.6)

        Obviously, we divided the discussion into two cases as follows.

        Case 1. p > 1

        In this case, f ( u ) = u p is convex, and f 0 = lim u 0 u p ϕ ( u ) = 0 and f = lim u u p ϕ ( u ) = . From Corollary 1.2(a), there exists 0 < λ < λ such that (3.6) has at least one positive solution for λ < λ < λ .

        Case 2. p < 1

        In this case, f ( u ) = u p is concave, and f 0 = lim u 0 u p ϕ ( u ) = and f = lim u u p ϕ ( u ) = . From Theorem 1.1(iv), there exists 0 < λ < λ such that (3.6) has at least two positive solutions for λ < λ < λ .

        Remark 3.1 It is worth to point out that our results only partly generalize the results of Habet and Omari [9] and Pan [12], since f ( u ) is more general than e u , u p and due to the limitation of the fixed point index method.

        Remark 3.2 Since f ( u ) in (1.1) is autonomous, it is not difficult to show that the solutions of (1.1) are symmetric around 1 2 , see [2, 12]. It follows that x 0 = 1 2 in the proof of Theorem 1.1, and we can set τ i = 1 4 , i = 1 , 2 and σ = 1 2 .

        Declarations

        Acknowledgements

        The authors are very grateful to the anonymous referee for his valuable suggestions. This work was supported by the NSFC (No. 11361054, No. 11201378), SRFDP (No. 20126203110004), Gansu provincial National Science Foundation of China (No. 1208RJZA258).

        Authors’ Affiliations

        (1)
        Department of Mathematics, Northwest Normal University

        References

        1. Atkinson FV, Peletier LA, Serrin J: Ground states for the prescribed mean curvature equation: the supercritical case. Math. Sci. Res. Inst. Publ. 12. In Nonlinear Diffusion Equations and Their Equilibrium States, I. Springer, New York; 1988:51-74. (Berkeley, CA, 1986)View Article
        2. Cano-Casanova S, López-Gómez J, Takimoto K: A quasilinear parabolic perturbation of the linear heat equation. J. Differ. Equ. 2012, 252: 323-343. 10.1016/j.jde.2011.09.018View Article
        3. Coffman C, Ziemer W: A prescribed mean curvature problem on domains without radial symmetry. SIAM J. Math. Anal. 1991, 22(4):982-990. 10.1137/0522063MathSciNetView Article
        4. Pan H, Xing R: Sub- and supersolution methods for prescribed mean curvature equations with Dirichlet boundary conditions. J. Differ. Equ. 2013, 254: 1464-1499. 10.1016/j.jde.2012.10.025MathSciNetView Article
        5. Bereanu C, Mawhin J: Boundary-value problems with non-surjective ϕ -Laplacian and one-sided bounded nonlinearity. Adv. Differ. Equ. 2006, 11(1):35-60.MathSciNet
        6. Bonheure D, Habets P, Obersnel F, Omari P: Classical and non-classical solutions of a prescribed curvature equation. J. Differ. Equ. 2007, 243: 208-237. 10.1016/j.jde.2007.05.031MathSciNetView Article
        7. Hai DD, Schmitt K, Shivaji R: Positive solutions of quasilinear boundary value problems. J. Math. Anal. Appl. 1998, 217: 672-686. 10.1006/jmaa.1997.5762MathSciNetView Article
        8. Hai DD, Schmitt K, Shivaji R: On the number of solutions of boundary value problems involving the p -Laplacian. Electron. J. Differ. Equ. 1996, 1: 1-9.MathSciNet
        9. Habets P, Omari P: Multiple positive solutions of a one-dimensional prescribed mean curvature problem. Commun. Contemp. Math. 2007, 9(5):701-730. 10.1142/S0219199707002617MathSciNetView Article
        10. Kusahara T, Usami H: A barrier method for quasilinear ordinary differential equations of the curvature type. Czechoslov. Math. J. 2000, 50(125):185-196.MathSciNetView Article
        11. Manásevich R, Mawhin J: Boundary value problems for nonlinear perturbations of vector p -Laplacian-like operators. J. Korean Math. Soc. 2000, 37(5):665-685.MathSciNet
        12. Pan H: One-dimensional prescribed mean curvature equation with exponential nonlinearity. Nonlinear Anal. 2009, 70: 999-1010. 10.1016/j.na.2008.01.027MathSciNetView Article
        13. Pan H, Xing R: Time maps and exact multiplicity results for one-dimensional prescribed mean curvature equations. Nonlinear Anal. 2011, 74: 1234-1260. 10.1016/j.na.2010.09.063MathSciNetView Article
        14. Wang H: On the number of positive solutions of nonlinear systems. J. Math. Anal. Appl. 2003, 281: 287-306. 10.1016/S0022-247X(03)00100-8MathSciNetView Article
        15. Wang H: On the existence of positive solutions for semilinear elliptic equations in the annulus. J. Differ. Equ. 1994, 109: 1-7. 10.1006/jdeq.1994.1042View Article
        16. Deimling K: Nonlinear Functional Analysis. Springer, Berlin; 1985.View Article

        Copyright

        © Lu et al.; licensee Springer. 2014

        This article is published under license to BioMed Central Ltd. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly credited.